THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF CREATOTHERAPY AS A METHOD OF SOCIAL WORK - Демченко, Ірина; Ревнюк, Наталія; Іващенко, Катерина; Соболенко, Ольга (SWorldJournal, 2024)
The article discusses the theoretical foundations and basic principles of the use of creatotherapy in social work. The relevance of using this method for psychological and pedagogical support, recovery and harmonious development of the individual is empha